Fatigue Crack Propagation in Ceramic Wheel Used For Gas Turbine - JASIM, HAIDER HADI (Basrah Journal for Engineering Sciences, 2015)
This paper studies and compared the fatigue crack propagation rate da/dN for three kinds of ceramic wheel (model A, model B, and model C) made of Si3N4 ceramic with different additives used for gas turbine application. The stress intensity factor range was calculated using finite element method and then compared with analytical approximate approaches. Experimental fatigue test was carried out on the three specimens taken from the models. As a result, the types of additives effect on fatigue crack propagation rate. The model A has the highest da/dN values and model C exhibits the lower values of da/dN.